KINERJA KEUANGAN BANK UMUM SYARIAH DI INDONESIA PERIODE 2016-2019 - Cut Ermiati; Dita Amanah; Fauzia Agustini; Cut Rianita Nurjannah Putri; Dedy Ansari Harahap (Universitas Pendidikan Nasional, 2020)
Big or small the level of profits obtained by the company or profitability is a ratio inmeasuring the effectiveness of management as a whole. High level of profitabilitymeans that the condition of a company is good or healthy. Based on previous researchthat there are factors that can affect the ups and downs of profitability, namely theproblematic financing factors (Non Performing Financing) and capital adequacy(Capital AdequacyRatio).The population of this study is all Islamic banks that are included in the category ofIslamic Commercial Banks registered with the Financial Services Authority with a totalpopulation of 14 banks. The sampling technique used is saturated sampling with a totalsample of 182 data.The data analysis technique in this research is multiple regression models, the resultsof Non Performing Financing have a negative and significant effect on Return OnAssets and Capital Adequacy Ratio has no effect on Return On Assets. Keywords: Return On Assets (ROA), Non Performing Financing (NPF), andCapital Adequacy Ratio (CAR).